Eksistensi varietas bahasa Inggris dan bahasa Inggris standar - Floris, Flora Deborah (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2010)
English is not only used by people from ENL (English as a Native Lan- guage) countries to communicate with people from ESL (English as a Second Lan- guage) and EFL (English as a Foreign Language) countries or vice versa, but it even functions as a lingua franca among non-native speakers. As a result, English varie- ties or Englishes emerged. This paper proposes an argument that the coexistence of both standard and varieties of English is equally important.